Molecular Characterization of the Multiple Interactions of SpsD, a Surface Protein from Staphylococcus pseudintermedius, with Host Extracellular Matrix Proteins - FOSTER, TIMOTHY (My University, 2013)
Staphylococcus pseudintermedius, a commensal and pathogen of dogs and occasionally of humans, expresses surface proteins potentially involved in host colonization and pathogenesis. Here, we describe the cloning and characterization of SpsD, a surface protein of S. pseudintermedius reported as interacting with extracellular matrix proteins and corneocytes. A ligand screen and Western immunoblotting revealed that the N-terminal A domain of SpsD bound fibrinogen, fibronectin, elastin and cytokeratin 10. SpsD also interfered with thrombin-induced fibrinogen coagulation and blocked ADP-induced platelet aggregation. The binding site for SpsD was mapped to residues 395–411 in the fibrinogen γ-chain, while binding sites in fibronectin were localized to the N- and C-terminal regions. SpsD also bound to glycine- and serine-rich omega loops within the C-terminal tail region of cytokeratin 10. Ligand binding studies using SpsD variants lacking the C-terminal segment or containing an amino-acid substitution in the putative ligand binding site provided insights into interaction mechanism of SpsD with the different ligands. Together these data demonstrate the multi-ligand binding properties of SpsD and illustrate some interesting differences in the variety of ligands bound by SpsD and related proteins from S. aureus.
PUBLISHED
Keywords: Staphylococcus pseudintermedius